Corruption speeches in the votes at the Supreme Federal Court (2015-2017) - Daniel Fonseca Fernandes; Tainan Bulhões Santana (Revista Brasileira de Direito Processual Penal)
This article analyzes the speeches about corruption in the votes of the Supreme Federal Court, between the years 2015 and 2017. This empirical research has a qualitative character and uses bibliographic and documentary research techniques, through the collection and analysis of Supreme collegiate decisions, referring to the crime of passive corruption. The research is guided by the following problem: which speeches about corruption were mobilized by the ministers of the Supreme Federal Court in the collegiate judgments between the years 2015 and 2017? To position these speeches, the work reflects on central categories of Brazilian social thought, such as “patrimonialism”, questioning their uses by jurists. The Supreme Court's performance is contextualized based on the Mensalão and Lava Jato phenomena and the pressure for certain results exerted on the Court. Relations with the press, pressure from judicial agencies and internal disputes are highlighted as important factors in understanding decisions.